2003
DOI: 10.1038/sj.ejcn.1601729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interaction between the C677T 5,10-methylenetetrahydrofolate reductase polymorphism and serum B vitamins on homocysteine levels in pregnant women

Abstract: Objective: The purpose of this study was to investigate the effect of the interaction between the C677T mutation in the 5,10-methylenetetrahydrofolate reductase (MTHFR) genotypes and serum levels of B vitamins on serum homocysteine levels in pregnant women. Design: A cross-sectional study. Setting: Ewha Womans University Hospital, Seoul, Korea. Subjects: A total of 177 normal pregnant women, 24.671.1 weeks of gestation, in a 6-month period during [2001][2002]. Interventions: Serum vitamin B 2 , vitamin B 6 , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
(43 reference statements)
1
14
0
Order By: Relevance
“…Another limitation of the study is that we did not evaluate the association between homocysteine levels and Results are the mean±SD or mean±SEM for differences or n (%) as stated a The CC genotype had significantly higher rate of prevalent fracture than the AA and AC genotypes, P=0.024 (chi-square test) b Analysis adjusted for baseline age and weight, 1 year hip BMD, prevalent fracture, calcium treatment, and compliance with study tablets some medications, such as anti-epileptic, lipid-lowering, and antihypertensive drugs, that have been reported to influence homocysteine levels [40,41]. Consistent with previous analyses [15,42,43], an increased plasma homocysteine level was observed in those with the MTHFR C677T TT genotype and either low folate intake or low riboflavin intake. These data support that this polymorphism impairs the MTHFR enzyme activity and thus the conversion of homocysteine to methionine, especially in the presence of suboptimal levels of dietary folate and riboflavin, which are both necessary for the conversion.…”
Section: Discussionsupporting
confidence: 78%
“…Another limitation of the study is that we did not evaluate the association between homocysteine levels and Results are the mean±SD or mean±SEM for differences or n (%) as stated a The CC genotype had significantly higher rate of prevalent fracture than the AA and AC genotypes, P=0.024 (chi-square test) b Analysis adjusted for baseline age and weight, 1 year hip BMD, prevalent fracture, calcium treatment, and compliance with study tablets some medications, such as anti-epileptic, lipid-lowering, and antihypertensive drugs, that have been reported to influence homocysteine levels [40,41]. Consistent with previous analyses [15,42,43], an increased plasma homocysteine level was observed in those with the MTHFR C677T TT genotype and either low folate intake or low riboflavin intake. These data support that this polymorphism impairs the MTHFR enzyme activity and thus the conversion of homocysteine to methionine, especially in the presence of suboptimal levels of dietary folate and riboflavin, which are both necessary for the conversion.…”
Section: Discussionsupporting
confidence: 78%
“…Several groups of investigators, including our own, have reported an inverse association between homocysteine and folate concentration in pregnant women (Guerra-Shinohara et al, 2002;Kim et al, 2004;Park et al, 2004;Lindblad et al, 2005). Elevated plasma homocysteine during pregnancy has been implicated in placental vascular changes in preeclampsia (de Vries et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…When mothers' allergic status was restricted to asthma, the prevalence was closer to the observed prevalence of atopy in the children and there remained no evidence of an association with the MTHFR genotype. We did not have objective measurements of maternal folate status based on blood samples in this study but there is good evidence that MTHFR C677T is a functional polymorphism that is linked to plasma homocysteine levels and modified by dietary folate status [31]. Although, a deficiency state associated with TT homozygosity might influence dietary behaviour, there was no evidence from our analyses that maternal folate intake varied by the MTHFR C677T genotype.…”
Section: Discussionmentioning
confidence: 93%